TRACING VISHNU THROUGH ARCHAEOLOGICAL REMAINS AT THE WESTERN SLOPE OF MOUNT LAWU - Heri Purwanto; Kadek Dedy Prawirajaya R. (Pusat Penelitian Arkeologi Nasional, 2020)
Abstract. To date, The West Slope area of Mount Lawu has quite a lot of archaeological remains originated from Prehistoric Period to Colonial Period. The number of religious shrines built on Mount Lawu had increased during the Late Majapahit period and were inhabited and used by high priests (rsi) and ascetics. The religious community was resigned to a quiet place, deserted, and placed far away on purpose to be closer to God. All religious activities were held to worship Gods. This study aims to trace Vishnu through archaeological remains. Archaeological methods used in this study are observation, description, and explanation. Result of this study shows that no statue has ever been identified as Vishnu. However, based on archeological data, the signs or symbols that indicated the existence of Vishnu had clearly been observed. The archeological evidences are the tortoise statue as a form of Vishnu Avatar, Garuda as the vehicle of Vishnu, a figure riding Garuda, a figure carrying cakra (the main weapon of Vishnu), and soles of his feet (trivikrama of Vishnu). Keyword: Mount Lawu, Symbols, Vishnu Abstrak. Kawasan Lereng Barat Gunung Lawu hingga saat ini cukup banyak menyimpan tinggalan arkeologi, baik yang berasal dari Masa Prasejarah hingga Masa Kolonial. Jumlah bangunan suci keagamaan yang didirikan mengalami peningkatan ketika masa Majapahit Akhir, yang diyakini dibangun dan dihuni oleh kaum rsi dan pertapa. Kaum agamawan tersebut sengaja mengundurkan diri ke tempat yang sunyi, sepi, dan jauh dari keramaian untuk mendekatkan diri kepada Tuhan. Sudah barang tentu kegiataan keagamaan yang dilakukan adalah pemujaan terhadap para dewa. Kajian ini ingin menelusuri jejak keberadaan Wisnu melalui tinggalan arkeologi yang ada. Untuk menyelesaikan permasalahan tersebut digunakan metode arkeologi yakni observasi, deskripsi, dan ekplanasi. Hasil dari kajian ini menunjukkan bahwa hingga sekarang belum ditemukan adanya arca Wisnu, namun berdasarkan tanda dan simbol yang berkaitan dengan Wisnu jelas teramati. Bukti-bukti tersebut adalah arca kura-kura yang merupakan salah satu wujud dari avatara Wisnu, Garuda wahana dari Wisnu, tokoh menunggang garuda, tokoh membawa cakra (senjata utama dari Wisnu), dan telapak kaki (trivikrama Wisnu). Kata kunci: Gunung Lawu, Simbol, Wisnu